Maternal choline supplementation during murine pregnancy modulates placental markers of inflammation, apoptosis and vascularization in a fetal sex-dependent manner. (May 2017) - Kwan, Sze Ting (Cecilia); King, Julia H.; Yan, Jian; Jiang, Xinyin; Wei, Emily; Fomin, Vladislav G.; Roberson, Mark S.; Caudill, Marie A.
Abstract: Introduction: Normal placental vascular development is influenced by inflammatory, angiogenic and apoptotic processes, which may be modulated by choline through its role in membrane biosynthesis, cellular signaling and gene expression regulation. The current study examined the effect of maternal choline supplementation (MCS) on placental inflammatory, angiogenic and apoptotic processes during murine pregnancy. Method: Pregnant dams were randomized to receive 1, 2 or 4 times (X) the normal choline content of rodent diets, and tissues were harvested on embryonic day (E) 10.5, 12.5, 15.5 or 18.5 for gene expression, protein abundance and immunohistochemical analyses. Results: The choline-induced changes in the inflammatory and angiogenic markers were a function of fetal sex. Specifically, 4X (versus 1X) choline reduced the transcript ( P  ≤ 0.05) and protein ( P  ≤ 0.06) expression of TNF-a and IL-1β in the male placentas at E10.5 and E18.5, respectively. In the female placentas, 4X (versus 1X) choline modulated the transcript expression of Il1b in a biphasic pattern with reduced Il1b at E12.5 ( P  = 0.045) and E18.5 ( P  = 0.067) but increased Il1b at E15.5 ( P  = 0.031). MCS also induced an upregulation of Vegfa expression in the female placentas at E15.5 ( P  = 0.034; 4X versus 2X) and E18.5 ( P  = 0.026; 4X versus 1X). MCS decreased ( P  = 0.011; 4X versus 1X) placental apoptosis at E10.5. Additionally, the luminal area of the maternal spiral arteries was larger ( P  ≤ 0.05; 4X versus 1X) in response to extra choline throughout gestation. Discussion: MCS during murine pregnancy has fetal sex-specific effects on placental inflammation and angiogenesis, with possible consequences on placental vascular development. Highlights: Choline alters the abundance of inflammatory, angiogenic and apoptotic markers in the mouse placenta. The placental responses to maternal choline supplementation are fetal sex- and gestational day-dependent. Maternal choline supplementation increases the maternal spiral artery luminal area, which may enhance placental perfusion.